Characterization of “School of Waters”: literature review and perspectives for research (Research, Society and Development, 2021)
The present study develops a reflection on the characterization of the School of Waters in the region of Mato Grosso do Sul and highlights the importance of systematizing discussions on pedagogical and management aspects of this context. The study is of a qualitative nature with characteristics of a literature review. Three databases were used: CAPES Thesis and Dissertations Catalog, CAPES Journals Portal and Scientific Electronic Library Online (SciELO), the discussions in this text presented are based on articles, dissertations and theses, with a time frame in the last few ten years (2010-2020). According to the searches, it can be seen that the community that lives on the banks of the rivers is influenced by changes in nature, in relation to river floods and droughts, which impact the routine of schools, while children in these regions are known to help their parents with work. In total, 6 studies were identified that investigated the context of the Schools of Waters in the pedagogical and administrative dimensions. In short, there was an increase in studies that deal with the theme, which points to the need to enhance research in order to provide improvements for the communities that live on the banks of rivers and their tributaries.